The Effect of Guided Discovery Learning Method Toward Students’ Ability in Understanding Math Concept - Guswita Sari; Nurhizrah Gistituati; Hendra Syarifuddin (International Journal of Educational Dynamics, 2019)
One of the most important abilities in learning mathematics for elementary students is understanding math concepts. However, elementary students’ ability to understand the math concepts in Padang is poor. The reason behind the problem is caused by inappropriate learning methods used by teachers, such as memorization. Based on this problem, the researchers conducted experimental research using guided discoverylearning methods to overcome the problem and identify its effects on the students’ ability to understand math concepts. The populations are all elementary students at grade 5in Padang who were enrolled in group V, Kuranji sub-district, semester II academic year 2017/2018. The sample selection is done by random sampling. The experimental class is grade 5 students atelementary school 44 Kalumbuk and control class is grade 5 students at elementary school 20 Kalumbuk, Padang. The data are obtained from the initial ability tests and questions in understanding math concepts. The data are analyzed using the t-test and two-way ANOVA for interaction. The results of the analysis show that: (1) guided discovery learning methods is better than conventional learning, (2) students’ math concepts understanding with high and low initial abilities taught by guided discovery learning method gets better resultcompared to conventional learning, and (3) there is no interaction between learning through guided discovery learning method and initial abilities in influencing students' ability to understand math concepts.